Potentials of cultural-historical and tourism heritage for the development of tourism in the Timok region - Bugarin , Dejan; Krsmanović Veličković, Sanja; Tucović, Miloš (Serbian Journal of Management, 2021)
In recent years, the term "industrial tourism" has been increasingly used in the literature. It describes an area that includes industrial monuments and abandoned buildings, and above all rare ones that are still in function. Industrial tourism includes all plants used for food processing, wood processing and textile industry, there are also mills, ports, mines, car and aviation industry, shipyards, etc. Within the doctoral dissertation entitled "Potentials of cultural-historical and economic heritage for the development of industrial tourism in the Timok region", a research was conducted that deals with the growing interest of industrial tourism in Eastern Serbia, more precisely in the Timok region. This branch of tourism is no longer a sphere of interest only for certain groups of technical experts, but also for regular tourists who are interested in touring certain regions. The aim of the research is to present the possibilities for the development of industrial tourism in the Timok region, as well as to obtain data on the current situation. The research is based on the experiential information of tourism workers who, due to the nature of their work and interests, are relevant to the proposed topic. The surveyed respondents are employed in the field of tourism in various positions, as well as students who are educated in the field of tourism. The data obtained during the research indicate respondents believe that the media do not sufficiently inform potential tourists about industrial tourism attractions, the potential of the tourist offer, but also about the Timok region itself, both locally and beyond, in Serbia and abroad. Such data indicate the possibility of improvement through the application of an adequate strategy to promote and inform potential users, as well as the insufficient usage of the industrial potential of the region itself. Investing certain resources in the marketing and development of industrial tourism would create additional demand, and this would result in the improvement of the tourist offer. Valorization of industrial heritage in Eastern Serbia can stimulate regional identity, revitalize the area and create additional tourist attractions. Plans and results from certain projects of this type are very important for the region, but also for the state.
Keywords: Tourism; industrial tourism; development; Timok region; Serbia